Implementing a personalized medicine program in a community health system. (22nd October 2018) - Dressler, Lynn G; Bell, Gillian C; Ruch, Karl D; Retamal, Jennifer D; Krug, Paige B; Paulus, Ronald A
The implementation of a de novo personalized medicine program in a rural community health system serving an underserved population is described. Focusing on the safe use of drugs impacted by genetic variations in the non-oncology setting, we first addressed drug–gene pairs designated by the US FDA in black-box warnings (codeine, clopidogrel, abacavir, carbamazepine). The program's first success was a policy change to remove codeine from the pediatric formulary, rather than a testing recommendation. Pilot studies were then conducted with primary care providers to get them familiar with pharmacogenetic testing, and a consultative outpatient clinic for patients was developed. The assessment, planning, implementation, challenges, successes and lessons learned are described.